Is Bauman's "liquid modernity" influencing the way we are doing science? - Mattiazzi, Ramona Alicia (2021)
This commentary analyzes the possible effects of lightness—a typical attribute of modern (liquid) society, according to Bauman—on the way we are doing science. We share our opinion in an attempt to discern whether some unwanted practices that may affect our scientific results (such as technology misuse, bonus rewards, publishing under pressure, or indolence for getting accurate results) can be attributed, at least partially, to the liquid characteristic of modern society. We also examine whether the different systems that support science favor these actions, conspiring against what should be the primary goal of science: the search for truth. We finally consider several aspects that should be taken into account to rescue science from the intrusion of weightless actions.